Diagnosing NAFLD in Diabetic Patients with circRNA CDR1as: An Analysis of Efficacy and Correlation with Glucose Metabolism: CircRNA CDR1as: NAFLD Diagnostic Biomarker in Diabetes - Zhang, Jingjing; Zhang, Xinzhi; Apaer, Shadike; Zhang, Shuo; Liang, Guangyou; Dong, Qiang; Huang, Jinchuang; Li, Tao; Cao, Xinling (Journal of Medical Biochemistry, 2025)
Objective: To explore the expression characteristics and diagnostic efficacy of circRNA CDR1as, as well as its correlation with glucose metabolism disorders in patients with diabetes mellitus (DM) complicated by non-alcoholic fatty liver disease (NAFLD), so as to provide a novel target for precision diagnosis and treatment.Methods: From May 2024 to August 2025, 74 DM patients complicated by NAFLD (research group) and 71 patients with uncomplicated DM (control group) were included. Serum CDR1as levels were detected by quantitative reverse transcription polymerase chain reaction (qRT-PCR), fasting insulin (FINS) by chemiluminescence, fasting blood glucose (FPG) by a blood glucose meter, and glycosylated hemoglobin (HbA1c) by high-performance liquid chromatography (HPLC). The homeostasis model assessment of insulin resistance (HOMA-IR) was calculated. The diagnostic efficacy of CDR1as was evaluated by receiver operating characteristic (ROC) curves, and the correlation between CDR1as and glucose metabolism indexes was analyzed.Results: CDR1as was expressed at an elevated level (29.00% greater) in the research group than in controls (P